Memes, racismo recreativo e educação histórica : um estudo de caso na rede pública de educação de Mato Grosso - MT - Rocha, Marcelo Nunes (2022)
The research presented here aims to investigate eighth-year students from the state network, the historical ideas of those in education in Mato Grosso about the racism conveyed in internet memes, while also exploring the possibilities of combating racism through this digital artifact so consumed by young people. The information provided by students in the form of a digital questionnaire will be analyzed in the light of Jörn Rüsen's theory and his concept of "historical consciousness", and the area of History Education, which has historian Peter Lee as one of the main exponents, creator of Fundamental conceptual tools for "this study concepts such as “substantives" and "second order". Finally, they use Professor Adilson Moreira's concept of "recreational racism" to understand the fundamentals of harmful humor propagated by racist memes.